Perpaduan dan Komposisi Masyarakat dari Perspektif Ibn Khaldun - Awang, Jaffary (Jurnal Usuluddin, 2001)
Integration amongst the multi-racial society is an important issue. Many scholars have suggested formulas for the integration of a multi-religious society. In this article some of Ibn Khaldun's ideas regarding the unity amongst society will be critically discussed. His approaches and concepts such as the role of 'Asabiyyah in the society during his time will be compared with some western sociologist views. In fact this article is trying to show that Ibn Khaldun's ideas about the development of society is still relevant to the contemporary situation.